Systematic review and classification of: MOT Robust youth 12 – 16 - Rye, Marte; Kaiser, Sabine; Martinussen, Monica (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2021)
Background: MOT Robust youth 12 – 16 is a universal preventive and health promoting program targeting youth aged 12-16 years. The goal is to develop warmer and safer communities by developing robust youth that include everyone. The program consists of twelve class visits over the course of all three years in secondary school where various topics are discussed and reviewed in a structured way. In addition, there are other activities during the school year. The initiative is owned by the MOT Foundation, an idealistic organization that was established in 1997 by Norwegian top athletes.Methods: This review is based on a systematic literature search in the databases Embase, Medline, Psykinfo, NORART, Cochrane, Cristin, NORA, SCOPUS and SweMed. International databases on evidence have also been searched, as well as information about the intervention from the program provider. Results from literature searches and the other information obtained were reviewed to identify Nordic effect studies, international systematic reviews and eventually other Norwegian studies of the intervention.Results: The results presented in this paper consist of assessments of the intervention´s description, available studies, quality of research methodology and quality of implementation. MOT Robust youth 12-16 is considered to be satisfactory described and it is founded on widely accepted theories. However, no Nordic effect studies have been identified. This review describes four Norwegian studies, but none of these are of the scientific quality necessary to draw conclusions about the effect of the intervention.Conclusion: MOT Robust youth 12-16 is classified at evidence level 2 – Theoretically-based interventions.
Keywords: School-related difficulties; Universal Preventive Program; Systematic review; School Program